INCREASING THE ABILITY TO APPRECIATE POETRY WITH THE STRATTA LEARNING MODEL IN CLASS XI FA2 STUDENTS ENREKANG STATE 3 HIGH SCHOOL - Miftahul Jannah Ismail; Sitti Rabiah; Kasma F. Amin (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to describe the process of implementing the Stratta learning model in appreciating poetry and analyzing the improvement in students' abilities. The method used in this research is a type of Classroom Action Research (PTK). Several stages carried out in this research include planning, implementing actions, observing and reflecting. The learning process by applying the Stratta learning model experienced an increase in activity, namely in cycle 1 the average value of activity reached 74.5 % and increased in cycle 2 to 84%. Therefore, by applying the Stratta model in learning to appreciate poetry, it is able to activate students. The learning outcomes obtained by applying the Stratta learning model, namely cycle 1, have an average value of 80% with categories of 5% sufficient, 72% good, 23% very good. Based on these scores, there are still students who have not obtained the KKTP score so it is deemed necessary to continue to cycle 2. The average score for cycle 2 increased to 88% with 23% in the good category and 77% in the very good category, with all students achieving the KKTP score. The results of this research prove that using the stratta model in appreciating poetry can improve student learning outcomes.